If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3r+6*4=4r-12*6
We move all terms to the left:
3r+6*4-(4r-12*6)=0
We add all the numbers together, and all the variables
3r-(4r-72)+6*4=0
We add all the numbers together, and all the variables
3r-(4r-72)+24=0
We get rid of parentheses
3r-4r+72+24=0
We add all the numbers together, and all the variables
-1r+96=0
We move all terms containing r to the left, all other terms to the right
-r=-96
r=-96/-1
r=+96
| x²-10x+16=0 | | 7(4+x)+2=5(x+8) | | k+-3/8=-7/8 | | 12x-7=9x+17 | | -9p+-20=-65 | | 43.25/1.25-7=k | | 6-10m=7m | | |x|=-x | | x/6=12/5 | | 3(5x-7)=7x+13 | | -i=1/i | | -(6r+8)+3=-(5r+8) | | 6=3s | | 8(x+2)-4(x-8)=8x+16-4x-32 | | 3.5+10m=8.14 | | 4n+18=-39 | | 3/6=12/w | | 10(k–89)=90 | | 7(v-5)-5v=-25 | | 13-2(2w+1)=5w-2(5+w | | 5c-7=4c | | X=9y=-2 | | 25 = c4– -23 | | 2/3(4)=2x | | 5(y+4)-2y=26 | | 0=50-y^2 | | (8y+14)^2=45 | | 0.7y+0.04=0.08y | | 5(12-2x)+7x=4(3x-2)-11x-8 | | -1+7k=20 | | 12z-3=9z+12 | | 10y+45=67y+79 |